2018
DOI: 10.2135/cropsci2018.04.0232
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Grain Yield QTLs from Soft Winter Wheat Using a CIMMYT Spring Wheat Panel

Abstract: Validation of quantitative trait loci (QTLs) is an essential step in marker‐assisted breeding. The objectives of this study were to validate grain yield (GY) QTLs previously identified in soft red winter wheat (Triticum aestivum L.) through biparental and association mapping using the spring wheat association mapping initiative (WAMI) panel from CIMMYT, Mexico, and to identify allele combinations of the validated QTLs that resulted to the highest GY. Linked single‐nucleotide polymorphisms for IWA3560 (3A), IWA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 36 publications
1
10
0
1
Order By: Relevance
“…Previously, some QTL validation studies for grain yield in wheat showed the potential of using allele specific assays such as KASP ® [52] to select for lines with high yield potential. Lozada et al [53], for instance, developed marker assays for yield and component traits and used a diverse panel of spring wheat lines from CIMMYT, Mexico to validate the effects of yield-related loci previously identified in southern US winter wheat. They eventually showed the potential of developing molecular marker assays that could select for spring wheat lines with improved yield potential.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, some QTL validation studies for grain yield in wheat showed the potential of using allele specific assays such as KASP ® [52] to select for lines with high yield potential. Lozada et al [53], for instance, developed marker assays for yield and component traits and used a diverse panel of spring wheat lines from CIMMYT, Mexico to validate the effects of yield-related loci previously identified in southern US winter wheat. They eventually showed the potential of developing molecular marker assays that could select for spring wheat lines with improved yield potential.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, some QTL validation studies for grain yield in wheat showed the potential of using allele specific assays such as KASP 1 [57] to select for lines with high yield potential. Lozada et al [58] developed marker assays for yield and component traits and used a diverse panel of spring wheat lines from the International Maize and Wheat Improvement Center (CIMMYT) in Mexico to validate the effects of yield-related loci previously identified in southern US winter wheat. They eventually showed the potential of developing molecular marker assays that could select for spring wheat lines with improved yield potential.…”
Section: Plos Onementioning
confidence: 99%
“…For example, when there is a need to screen a sufficiently large plant population for a quantitative trait analysis, e.g., grain size or abiotic stress tolerance, considering replicated trials over multiple locations makes phenotyping laborious and technically challenging. In some cases, the labor-intensive and costly nature of conventional field phenotyping led many crop breeding programs to make a single measurement of final yield for replicated plots in multiple environments [ 9 , 10 , 11 ]. However, yield itself is one of the most poorly inherited traits in crop breeding [ 12 ].…”
Section: Introductionmentioning
confidence: 99%